Music, philosophy, and modernity - Bowie, Andrew (Cambridge Cambridge University Press, 2007)
Modern philosophers generally assume that music is a problem to which philosophy ought to offer an answer. Andrew Bowie's Music, Philosophy, and Modernity suggests, in contrast, that music might offer ways of responding to some central questions in modern philosophy. Bowie looks at key philosophical approaches to music ranging from Kant, through the German Romantics and Wagner, to Wittgenstein, Heidegger and Adorno. He uses music to re-examine many ideas about language, subjectivity, metaphysics, truth and ethics, and he suggests that music can show how the predominant images of language, communication, and meaning in contemporary philosophy may be lacking in essential ways. His book will be of interest to philosophers, musicologists, and all who are interested in the relation between music and philosophy.Proposes an original approach to the understanding of musicConsiders many largely neglected and untranslated textsOffers new ways of questioning the predominant ideas about language in the analytical tradition of philosophy